Lessons from the recent publication scams - Shah, Afroz Ahmad (Current Science, 2014)
The article discusses growing number of scams by agencies, scientists and editors in publishing industry of China. It states that an authorship fee ranging from 1,600 dollars to 26,300 dollars, in journals indexed by Thomson Reuter's Science Citation Index, Thomson Reuter's Social Science Citation Index and Elsevier's Engineering Index. It mentions that that talent based system in academia can also motivate scientists to wrongly inflate their findings.